2019
DOI: 10.1016/j.jcp.2019.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Newman-Ziff algorithm for the bootstrap percolation: Application to the Archimedean lattices

Abstract: We propose very efficient algorithms for the bootstrap percolation and the diffusion percolation models by extending the Newman-Ziff algorithm of the classical percolation [M. E. J. Newman and R. M. Ziff, Phys. Rev. Lett. 85 (2000) 4104]. Using these algorithms and the finite-size-scaling, we calculated with high precision the percolation threshold and critical exponents in the eleven two-dimensional Archimedean lattices. We present the condition for the continuous percolation transition in the bootstrap perco… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 41 publications
0
21
0
Order By: Relevance
“…W 1 (p, L) is the wrapping probability in any one direction but not in the other direction. Critical exponents ν and β can be estimated from the scaling relations [28,29,26] Max dW (p, L) dp ∼ L 1/ν , dW (p, L) dp…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…W 1 (p, L) is the wrapping probability in any one direction but not in the other direction. Critical exponents ν and β can be estimated from the scaling relations [28,29,26] Max dW (p, L) dp ∼ L 1/ν , dW (p, L) dp…”
Section: Resultsmentioning
confidence: 99%
“…) A new site of the distorted lattice is chosen uniformly at random within the sampling domain. Two occupied nearest neighbors are set to be connected if and only if their Euclidean distance is smaller than the connection threshold d. In this work, the Newman-Ziff algorithm, which is much more efficient than brute-force methods when the percolation threshold is not known in advance [24,25,26], is used. In this algorithm, a set of average values Q(n) is obtained first, where Q(n) is any physical quantity such as the size of the largest cluster for a fixed number of occupied sites n. A value of Q(p) as a function of occupation probability p can be calculated by the binomial transformation:…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further variations involve correlated percolation [13,14], like for example drilling percolation [15,16]. In bootstrap percolation [17][18][19][20], sites and/or bonds are first occupied and then successively culled from a system if a site does not have at least k neighbors. Another important model of percolation, which is in a different universality class, is directed percolation [21][22][23][24], where connectivity along a bond depends upon the direction of the flow.…”
Section: Introductionmentioning
confidence: 99%
“…The DP and BP have been studied intensively on lattices [6,7,8,9,4,10,11,12,13,14,15,16,17]. In the ∆-regular Archimedean lattices and three-dimensional lattices (simple cubic, body-centered cubic, and face-centered cubic lattices), it was shown that the DP and BP have first-order percolation transitions with the percolation thresholds p c = 1 and p c = 0, respectively, if m > m c and k < (∆ + 1 − m c ), where m c = (∆ + 1)/2 (the only exception is the bounce lattice, which has m c = (∆ + 1)/2 + 1) [6,18,4,14,16,17]; otherwise, the DP and BP have second-order percolation transitions at finite p c (0 < p c < 1) with the same critical exponents as the CP [16,17] (exceptionally, the BP transition with m = m c = 6 in the face-centered cubic lattice is first-order [17]).…”
Section: Introductionmentioning
confidence: 99%